The Crime of Theft from a Restorative Justice Perspective: A Normative Study of Padang District Court Decision Number 134/Pid.B/2025/Pn Pdg - Nouvel Izza Fardana (UNISSULA Semarang, 2025)
Abstract. This research aims to analyze the application of restorative justice in minor theft cases based on the District Court of Padang Decision No. 134/Pid.B/2025/PN PDG, by examining the relevance of this approach to the Indonesian penal system, which is grounded in the values of Pancasila Justice. Restorative justice represents an alternative approach that emphasizes the restoration of relationships between the offender, the victim, and the community, rather than focusing solely on punishment (retribution). This concept places direct responsibility on the offender for his actions and provides the victim with the opportunity to obtain fair recovery and acknowledgment. This study employs a normative juridical method, using both the statute approach and the case approach. The data were analyzed through the examination of statutory regulations, legal principles, scholarly doctrines, and relevant court decisions. The normative approach was chosen because the focus of this research lies in studying the legal norms that govern the implementation of restorative justice in theft cases, both under the 1946 Criminal Code (KUHP) and the newly enacted 2023 National Criminal Code. The findings of this research indicate that the implementation of restorative justice is not an antithesis to the rule of law; rather, it serves as a corrective lens within criminal law that aims to harmonize legal certainty, justice, and utility. Within the framework of national law, restorative justice aligns with the principle of justicia cum misericordia—to punish when necessary and to restore when possible—while upholding human dignity as the ethical axis of the penal system. The application of this principle has proven effective in achieving a balance between victim protection and offender accountability, without disregarding the interests of public order.